2001
DOI: 10.1007/s002470100434
|View full text |Cite
|
Sign up to set email alerts
|

A normal sonogram does not exclude malrotation

Abstract: We present case reports of three recent patients to reinforce the argument that upper gastrointestinal series is the method of choice with which to document malrotation. It has been 9 years since there was a major discussion of this subject in the literature. Ultrasonography cannot confidently exclude malrotation. Radiographic study with contrast continues to be the best diagnostic tool.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
1
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 0 publications
0
23
1
3
Order By: Relevance
“…This group of 9 children represented 30% of the children with malrotation in whom the mesenteric vessels were visualized. Ashley et al [6] reported 1 case with similar findings, and Zerin and DiPietro [8] noted that 3 (33%) of 9 children with malrotation had a normal orientation of the mesenteric vessels. It is unclear why these reports differ from our results.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…This group of 9 children represented 30% of the children with malrotation in whom the mesenteric vessels were visualized. Ashley et al [6] reported 1 case with similar findings, and Zerin and DiPietro [8] noted that 3 (33%) of 9 children with malrotation had a normal orientation of the mesenteric vessels. It is unclear why these reports differ from our results.…”
Section: Discussionmentioning
confidence: 74%
“…In those cases where the SMV lies anterior to the SMA the incidence of malrotation decreases to 25% to 28% [2,3]. However, it has been shown by other authors that inversion of the SMV/SMA relationship can also be seen in patients with normal midgut rotation [5,6] and in patients with abdominal masses and distal ileocolic intussusception [5,7]. Furthermore, not all cases of malrotation have abnormal SMV/SMA orientation on US [2,6,8].…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…However, this inversion is neither specific nor sensitive enough. A normal sonogram does not exclude malrotation (10). There are also other data which show that sonography is a good screening tool that effectively rules out malrotation at risk for volvulus (7).…”
Section: Discussionmentioning
confidence: 99%